Gender differences in psychological responses to recovery after anterior cruciate ligament reconstruction before return to sport - Lisee, C.; Di Santi. J. S.; Chan, M.; Ling, J.; Erickson, K.; Shingles, M.; Kuenze, C. M. (Journal of Athletic Training, 2020)
Context: Female patients with anterior cruciate ligament reconstruction (ACLR) are less likely to return to sport than males. Psychological readiness predicts successful return to sport, but it is unclear if psychological experiences differ between males and females during recovery. Objective: To explore gender differences in psychological readiness factors of return to sport after ACLR. Design: Qualitative study. Setting: Laboratory. Patients or Other Participants: A total of 12 male (months since surgery = 6.2 ± 1.2) and 13 female (months since surgery = 6.4 ± 1.3) high school athletes with a history of ACLR. Data Collection and Analysis: Participants were interviewed before physician clearance to return to activity. Transcribed interviews were analyzed using deductive thematic coding of 5 themes identified from previous research (psychological distress, self-efficacy, locus of control, athletic identity, and fear of reinjury) and inductive secondary subthematic coding. Gender comparisons were generated within primary themes and secondary subthemes. Results: All deductive themes were consistently reinforced. Male and female participants reported fear of movement, loss of athletic identity, and motivational mindsets for return to sport and self-improvement. Males reported a stronger sense of internal locus of control using positive internal reinforcement, whereas females described balancing internal and external control and valuing external support systems. Male participants described mood changes influenced by physical and social limitations. Female participants closely monitored their emotions throughout recovery and were influenced by rehabilitation fluctuations. Conclusions: Male and female high school athletes described different psychological factors related to return to sport and locus of control as well as psychological distress. Gender-specific psychological interventions may be warranted to overcome psychological barriers after ACLR.